At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Let's find the antiderivatives of the function [tex]\( f(y) = -\frac{24}{y^{25}} \)[/tex].
### Step 1: Rewrite the Function
Rewrite the function in a more convenient form:
[tex]\[ f(y) = -24y^{-25} \][/tex]
### Step 2: Integrate
To find the antiderivative, we need to perform the integration:
[tex]\[ \int -24y^{-25} \, dy \][/tex]
We use the power rule for integration, which states:
[tex]\[ \int y^n \, dy = \frac{y^{n+1}}{n+1} + C \][/tex]
for any [tex]\( n \neq -1 \)[/tex]. Here, [tex]\( n = -25 \)[/tex]:
[tex]\[ \int -24y^{-25} \, dy = -24 \int y^{-25} \, dy \][/tex]
[tex]\[ \int y^{-25} \, dy = \frac{y^{-25+1}}{-25+1} = \frac{y^{-24}}{-24} \][/tex]
Therefore:
[tex]\[ -24 \int y^{-25} \, dy = -24 \cdot \frac{y^{-24}}{-24} = y^{-24} \][/tex]
Don't forget to add the constant of integration [tex]\( C \)[/tex]:
[tex]\[ \int -24y^{-25} \, dy = y^{-24} + C \][/tex]
So, the antiderivative [tex]\( F(y) \)[/tex] is:
[tex]\[ F(y) = y^{-24} + C \][/tex]
### Step 3: Check the Work
To verify, let's take the derivative of [tex]\( F(y) \)[/tex]:
[tex]\[ \frac{d}{dy}\left( y^{-24} + C \right) \][/tex]
Since the derivative of a constant [tex]\( C \)[/tex] is zero:
[tex]\[ \frac{d}{dy}\left( y^{-24} \right) = -24y^{-25} \][/tex]
So:
[tex]\[ \frac{d}{dy}\left( y^{-24} + C \right) = -24y^{-25} \][/tex]
Which matches the original function [tex]\( f(y) = -24y^{-25} \)[/tex].
### Conclusion
The antiderivatives of [tex]\( f(y) = -\frac{24}{y^{25}} \)[/tex] are:
[tex]\[ F(y) = y^{-24} + C \][/tex]
This confirms our solution is correct.
### Step 1: Rewrite the Function
Rewrite the function in a more convenient form:
[tex]\[ f(y) = -24y^{-25} \][/tex]
### Step 2: Integrate
To find the antiderivative, we need to perform the integration:
[tex]\[ \int -24y^{-25} \, dy \][/tex]
We use the power rule for integration, which states:
[tex]\[ \int y^n \, dy = \frac{y^{n+1}}{n+1} + C \][/tex]
for any [tex]\( n \neq -1 \)[/tex]. Here, [tex]\( n = -25 \)[/tex]:
[tex]\[ \int -24y^{-25} \, dy = -24 \int y^{-25} \, dy \][/tex]
[tex]\[ \int y^{-25} \, dy = \frac{y^{-25+1}}{-25+1} = \frac{y^{-24}}{-24} \][/tex]
Therefore:
[tex]\[ -24 \int y^{-25} \, dy = -24 \cdot \frac{y^{-24}}{-24} = y^{-24} \][/tex]
Don't forget to add the constant of integration [tex]\( C \)[/tex]:
[tex]\[ \int -24y^{-25} \, dy = y^{-24} + C \][/tex]
So, the antiderivative [tex]\( F(y) \)[/tex] is:
[tex]\[ F(y) = y^{-24} + C \][/tex]
### Step 3: Check the Work
To verify, let's take the derivative of [tex]\( F(y) \)[/tex]:
[tex]\[ \frac{d}{dy}\left( y^{-24} + C \right) \][/tex]
Since the derivative of a constant [tex]\( C \)[/tex] is zero:
[tex]\[ \frac{d}{dy}\left( y^{-24} \right) = -24y^{-25} \][/tex]
So:
[tex]\[ \frac{d}{dy}\left( y^{-24} + C \right) = -24y^{-25} \][/tex]
Which matches the original function [tex]\( f(y) = -24y^{-25} \)[/tex].
### Conclusion
The antiderivatives of [tex]\( f(y) = -\frac{24}{y^{25}} \)[/tex] are:
[tex]\[ F(y) = y^{-24} + C \][/tex]
This confirms our solution is correct.
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.